Gefahren ionisierender Strahlung für Mensch und Umwelt in Bezug auf kerntechnische Anlagen - Felix Hübner; Jennifer Jana Jung; Frank Schultmann (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2017)
Worldwide, nuclear fission is used to produce electricity. On the one hand, the low emission of CO2 is often mentioned as an advantage of this technology. On the other hand, warnings about the dangers of nuclear fission are mentioned. Consequently, an overview about the dangers of ionizing radiation to human beings as well as animals and the environment is important. However, the focus will be on possible health effects for humans with regards to nuclear power plants. In nuclear power plants, both natural types of radiation and artificially produced radiation occur. During normal operation, it is possible that small quantities of this ionizing radiation are released to the environment. In case of nuclear disasters or faults during decommissioning and dismantling processes the consequences of thereby emitted quantities can be even more severe. Reference nuclides vary by reactor type, operating stage and respective incident. At the beginning, different types of radiation and their characteristics and effects on the affected organism are explained. Sensitive organs are emphasized in this context. The individual risk is determined by numerous factors and therefore cannot be predicted. Based on scientific studies and medical publications the hazards of ionizing radiation are compiled. Effects of high exposure of ionizing radiation are well-investigated. Scientists are still divided over the connection between several diseases and the exposure to low doses of ionizing radiation. For this reason, the positions of different international organizations are critically contrasted in this study. – – Worldwide, nuclear fission is used to produce electricity. On the one hand, the low emission of CO2 is often mentioned as an advantage of this technology. On the other hand, warnings about the dangers of nuclear fission are mentioned. Consequently, an overview about the dangers of ionizing radiation to human beings as well as animals and the environment is important. However, the focus will be on possible health effects for humans with regards to nuclear power plants. In nuclear power plants, both natural types of radiation and artificially produced radiation occur. During normal operation, it is possible that small quantities of this ionizing radiation are released to the environment. In case of nuclear disasters or faults during decommissioning and dismantling processes the consequences of thereby emitted quantities can be even more severe. Reference nuclides vary by reactor type, operating stage and respective incident. At the beginning, different types of radiation and their characteristics and effects on the affected organism are explained. Sensitive organs are emphasized in this context. The individual risk is determined by numerous factors and therefore cannot be predicted. Based on scientific studies and medical publications the hazards of ionizing radiation are compiled. Effects of high exposure of ionizing radiation are well-investigated. Scientists are still divided over the connection between several diseases and the exposure to low doses of ionizing radiation. For this reason, the positions of different international organizations are critically contrasted in this study.
urn:nbn:de:swb:90-680306
Keywords: 330